Leadership and employee environmental performance: mediation test from model job demands-resources dan sustainability perspective in micro level - Alex Winarno; Silvy Sondari Gadzali; Daniel Kisahwan; Deni Hermana (Cogent Business & Management)
This study uses an explanatory survey research method to explore the role of sustainable leadership in smart campus transformation at the micro level on engagement and environmental performance. The survey was conducted randomly, involving 487 academic staff and lecturers from various study programs. Data analysis was conducted using Structural Equation Modelling (SEM). The results showed that leadership is an evolving resource in the digital transformation process at various higher education levels. Sustainable leadership ensures that the Health Impairment and Motivational Process run in line with the change orientation aimed at improving environmental performance. Both processes encourage academic staff and lecturers to engage in green activities. This research reinforces the concept that leadership plays a key role in improving environmental performance through engagement in sustainable activities, especially in the context of higher education. The integration between Job Demands-Resources (JD-R) theory and sustainability theory, which is the basis for the development of the concept of sustainable leadership, helps to understand how the role of a leader can influence the level of sustainable engagement and performance and create a healthier and more motivating work environment to achieve sustainable goals.